Plasma treatment by gliding arc discharge of dyes/dye mixtures in the presence of inorganic salts - Addou, Ahmed; Merouani, DR; Abdelmalek, F; Taleb, F; Martel, M; Semmoud, A (Arabian Journal of Chemistry, 2015)
The gliding arc discharge plasma (GAD) technique was used for discoloration and degradation of an anthraquinone dye Alizarin red S (ARS), an azo dye Orange G (OG) and their mixture. The influence of chloride and sulfate salts on the efficiency of treatment has also been stud- ied. The aim of this study is the discoloration and degradation by GAD of ARS, and OG and their mixture. The GAD plasma generated between two moist air metallic electrodes connected to a high volt- age produced chemical species and highly reactive molecules OH, NO ,O ,O 2 ,HO 2 ,H ,H 2 O 2 ,O 3 ... and other excited-state neutral molecules. The reactions of discoloration for ARS and OG fol- lowed pseudo-first-order kinetics. The apparent kinetic constants of bleaching were found equal to 0.014 and 0.013 min 1 and degradation of 0.008 and 0.010 min 1 , respectively for the ARS and OG. For mixtures, the rate of discoloration was 80% in 120 min of treatment for mixtures III, IV and V, while the rate of COD reduction was fast in the first 30 min since it varied between 35% and 40% for all mixtures but stabilized at 68% toward the end of the treatment. The addition of chloride salts and sulfate showed a decrease in the effectiveness of treatment. GAD treatment is perfectly suited to dyes treatment. It is an alternative method that is part of green chemistry and sustainable development objectives. ª 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Gliding arc discharge; Alizarin red S; Orange G; Mixtures; Treatment; Degradation